Dinamika Psychological Well-Being pada Dewasa Dini Tunanetra yang Sudah Bekerja di Medan - Winida Marpaung; Tiberias Antonius Cornelis Papilaya; Gebriela Surya; Ingrid Eldy Tanida; Wenny Veronica (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The goal of this study is to delve deeper into the definition of psychological well-being in blind persons, as well as to examine the dynamics of psychological well-being in people with visual impairments who are currently working. This study employs qualitative methodologies in order to provide a thorough description of the findings. In-depth interviews and observations were utilized to collect data, which were based on Ryff's (1989) theory of psychological well-being, which included the categories of self-acceptance, positive connections with others, independence, environmental mastery, life objectives, and personal progress. Three blind people who were already working were the focus of this investigation. The three participants were found to have a high level of psychological well-being in this investigation. The three participants who have accepted themselves and made peace with their position, as well as the fulfillment of other elements of psychological well-being, demonstrate this. This condition may have arisen as a result of the three individuals' impaired vision since childhood, if not from birth. One of the reasons the subject comes to terms with his condition is because of his good relationships with others.